Exterior algebra resolutions arising from homogeneous bundles - Fløystad, Gunnar (MATHEMATICA SCANDINAVICA, 2004)
We describe resolutions of general maps (resp. general symmetric and skew-symmetric maps) E^a → E(1)^b given by linear forms over the exterior algebra E. Via the BGG-correspondence we describe the associated coherent sheaves. We also show how representation theory of algebraic groups enables one to solve these types of problems for much larger classes of maps.